Dry synthesis of bi-layer nanoporous metal films as plasmonic metamaterial - Caligiuri, Vincenzo; Kwon, Hyunah; Griesi, Andrea; Ivanov, Yurii P.; Schirato, Andrea; Alabastri, Alessandro; Cuscunà, Massimo; Balestra, Gianluca; Luca, Antonio De; Tapani, Tlek; Lin, Haifeng; Maccaferri, Nicolò; et al. (Nanophotonics, 2024)
Nanoporous metals are a class of nanostructured materials finding extensive applications in multiple fields thanks to their unique properties attributed to their high surface area and interconnected nanoscale ligaments. They can be prepared following different strategies, but the deposition of an arbitrary pure porous metal is still challenging. Recently, a dry synthesis of nanoporous films based on the plasma treatment of metal thin layers deposited by physical vapour deposition has been demonstrated, as a general route to form pure nanoporous films from a large set of metals. An interesting aspect related to this approach is the possibility to apply the same methodology to deposit the porous films as a multilayer. In this way, it is possible to explore the properties of different porous metals in close contact. As demonstrated in this paper, interesting plasmonic properties emerge in a nanoporous Au-Ag bi-layer. The versatility of the method coupled with the possibility to include many different metals, provides an opportunity to tailor their optical resonances and to exploit the chemical and mechanical properties of components, which is of great interest to applications ranging from sensing, to photochemistry and photocatalysis.
Gesehen am 06.08.2024